Lung aeration reduces blood pressure surges caused by umbilical cord milking in preterm lambs - Blank, Douglas A.; Crossley, Kelly J.; Thiel, Alison; Rodgers, Karyn A.; Zahra, Valerie; Kluckow, Martin; Gill, Andrew W.; Polglase, Graeme R.; Hooper, Stuart B. (Frontiers in Pediatrics, 2023)
Background: Umbilical cord milking (UCM) at birth causes surges in arterial blood pressure and blood flow to the brain, which may explain the high risk of intraventricular haemorrhage (IVH) in extremely preterm infants receiving UCM. This high risk of IVH has not been reported in older infants. Objective: We hypothesized that lung aeration before UCM, reduces the surge in blood pressure and blood flow induced by UCM. Methods: At 126 days’ gestation, fetal lambs (N=8) were exteriorised, intubated and instrumented to measure umbilical, pulmonary, cerebral blood flows, and arterial pressures. Prior to ventilation onset, the umbilical cord was briefly (2-3s) occluded (8 times), which was followed by 8 consecutive UCMs when all physiological parameters had returned to baseline. Lambs were then ventilated. After diastolic pulmonary blood flow markedly increased in response to ventilation, the lambs received a further 8 consecutive UCMs. Ovine umbilical cord is shorter than the human umbilical cord, with ~10cm available for UCMs. Therefore, 8 UCMs/occlusions were done to match the volume reported in the human studies. Umbilical cord clamping occurred after the final milk. Results: Both umbilical cord occlusions and UCM caused significant increases in carotid arterial blood flow and pressure. However, the increases in systolic and mean arterial blood pressure (10 ±3 mmHg vs 3 ±2 mmHg, p=0.01 and 10 ± 4 mmHg vs 6 ± 2 mmHg, p=0.048, respectively) and carotid artery blood flow (17±6 ml/min vs 10±6 ml/min, p=0.02) were significantly greater when UCM occurred before ventilation onset compared with UCM after ventilation. Conclusions: UCM after ventilation onset significantly reduces the increases in carotid blood flow and blood pressure caused by UCM.